Acute Effects of Short-Term Warm Water Immersion on Arterial Stiffness and Central Hemodynamics - Sugawara, Jun; Tomoto, Tsubasa (Frontiers in Physiology, 2021)
Warm water immersion (WWI) has a potentially favorable effect on vascular health. However; the effects of short-term WWI on vascular function and central hemodynamics remain unclear. The present study aimed to determine the acute effects of short-term WWI on arterial stiffness and central hemodynamics in healthy men. Ten healthy men (27-57 years, 44±12 years of mean age) underwent 5-minute WWI (40-41ºC) at the heart level. Systemic hemodynamics and tympanic temperature were monitored during WWI. Furthermore, pulse wave velocity (PWV) and aortic hemodynamics were measured before and 10 minutes after WWI. Cardiac output (via the Modelflow method) increased (P=0.037), whereas tympanic temperature did not change (P=0.879) during WWI. After 5-minute WWI, heart rate and brachial diastolic blood pressure (BP) were significantly decreased. Aortic and leg PWV were decreased by 7.5% and 3.1%, respectively (P=0.006 and P=0.049). Femoral arterial blood flow was increased by 45.9% (P=0.002) and leg vascular resistance was decreased by 29.1% (P<0.001). Regarding central hemodynamic variables (estimated by general transfer function), aortic BP and augmentation index did not change significantly but the subendocardial viability ratio, an index of coronary perfusion, was increased (P=0.049). Our results indicate that a short-term WWI acutely improves aortic and peripheral arterial stiffness and coronary perfusion. Further studies to determine the interaction between the residual effect of a single bout of short-term WWI and chronic change (e.g., adaptation) in arterial stiffness and central hemodynamics are needed.